Research advances on antioxidation, neuroprotection, and molecular mechanisms of Lycium barbarum polysaccharides. Issue 4 (December 2021) - Wang, Cheng; Zhou, Liangxing; Mo, Mei; Kong, Xianglin; Chai, Zhengbin; Deng, Lei; Zhang, Junli; Cao, Kuan; Wei, Chuanfei; Xu, Li; Chen, Juanli; Han, Fabin
Lycium barbarum polysaccharides (LBPs) are the major polysaccharides extracted from L. barbarum, which is used in traditional Chinese medicine (TCM) for treating diseases. Studies have shown that LBPs have important biological activities, such as antioxidation, anti-aging, neuroprotection, immune regulation. LBPs inhibit oxidative stress, improve neurodegeneration and stroke-induced neural injury, increase proliferation and differentiation of neural stem cell, and promote neural regeneration. Here we have reviewed latest advances in the biomedical activities of LBPs and improved methods for the isolation, extraction, and purification of LBPs. Then, new discoveries to decrease oxidative stress and cellular apoptosis, inhibit aging progress, and improve neural repair in neurodegeneration and ischemic brain injury have been discussed in detail through in vitro cell culture and in vivo animal studies. Importantly, the molecular mechanisms of LBPs in playing neuroprotective roles are further explored. Lastly, we discuss the perspective of LBPs as biomedical compounds in TCM and modern medicine and provide the experimental and theoretical evidence to use LBPs for the treatment of aging-related neurological diseases and stroke-induced neural injuries.